2012
DOI: 10.1016/j.sjpain.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed radiofrequency in peripheral posttraumatic neuropathic pain: A double blind sham controlled randomized clinical trial

Abstract: Background and purpose Pulsed radiofrequency (PRF) is widely used for the treatment of chronic pain, although its mechanism of action is not known. The evidence of efficacy of PRF for neuropathic pain (NP) conditions is limited. A double-blind, randomized, sham-controlled parallel study was conducted to evaluate the efficacy and safety of PRF in the treatment of peripheral posttraumatic NP. Methods Forty-five patients with peripheral posttraumatic NP in their upper or lower limb were randomly assigned to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There are several successful case reports or case series of peripheral PRF used for sacroiliac joint pain,23 shoulder pain, inguinal pain, thoracic pain, knee joint pain, occipital neuralgia, and painful neuroma 3. Disappointingly, the only published sham-controlled RCT for peripheral neuropathic pain, reported by Akural et al, failed to demonstrate clinical efficacy 24. They could not perform a sample size calculation, and of 45 well selected patients with limb symptoms, only seven (including four sham-treated patients) achieved a >30% decrease in pain score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several successful case reports or case series of peripheral PRF used for sacroiliac joint pain,23 shoulder pain, inguinal pain, thoracic pain, knee joint pain, occipital neuralgia, and painful neuroma 3. Disappointingly, the only published sham-controlled RCT for peripheral neuropathic pain, reported by Akural et al, failed to demonstrate clinical efficacy 24. They could not perform a sample size calculation, and of 45 well selected patients with limb symptoms, only seven (including four sham-treated patients) achieved a >30% decrease in pain score.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Disappointingly, the only published sham-controlled RCT for peripheral neuropathic pain, reported by Akural et al, failed to demonstrate clinical efficacy. 24 They could not perform a sample size calculation, and of 45 well selected patients with limb symptoms, only seven (including four sham-treated patients) achieved a >30% decrease in pain score. Similarly, an RCT for trigeminal neuralgia involving 40 patients reported that only two of 20 patients had successful pain relief with PRF, 25 despite there being previous successful case reports of trigeminal PRF.…”
Section: Discussionmentioning
confidence: 99%